2012
DOI: 10.1051/0004-6361/201117458
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of O stars in NGC 2244 and the Monoceros OB2 association

Abstract: Aims. Our goal is to determine the stellar and wind properties of seven O stars in the cluster NGC 2244 and three O stars in the OB association Mon OB2. These properties give us insight into the mass loss rates of O stars. They allow us to both check the validity of rotational mixing in massive stars and to better understand the effects of the ionizing flux and wind mechanical energy release on the surrounding interstellar medium and its influence on triggered star formation. Methods. We collected optical and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
103
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 82 publications
13
103
1
Order By: Relevance
“…This result is combined and put in perspective with several other investigations of O-type stars in the Galaxy (Martins et al 2012(Martins et al , 2015Bouret et al 2012). Although this constitutes a set of heterogeneous studies, all the analyses use the same tool to determine the stellar parameters.…”
Section: The N Contentmentioning
confidence: 92%
See 1 more Smart Citation
“…This result is combined and put in perspective with several other investigations of O-type stars in the Galaxy (Martins et al 2012(Martins et al , 2015Bouret et al 2012). Although this constitutes a set of heterogeneous studies, all the analyses use the same tool to determine the stellar parameters.…”
Section: The N Contentmentioning
confidence: 92%
“…For the UV domain, we focus mainly on N v 1240, Si iv 1394-1403, and C iv 1548-1551, and when FUSE spectra are available, we consider C iv 1169 and C iii 1176 as additional diagnostics to those lines for mass-loss rate determination. A single value ofṀ should allow a good fit of both types of lines even though a study by Martins et al (2012) has shown that this was not always the case. In our analysis, we reach a general agreement between UV and Hα lines by playing on other parameters such as the clumping or the β.…”
Section: Modellingmentioning
confidence: 99%
“…HD 149757 (ζ Oph; O9.2 IVnn, Sota et al 2011; v sin i ∼ 378 km s −1 ) has been studied by Villamariz & Herrero (2005). In addition, the CNO abundances of two O-type supergiants, two O dwarfs, five additional O giants, and four other O-stars with v sin i ≥ 200 km s −1 have been derived by Bouret et al (2012), and Martins et al (2012bMartins et al ( , 2015b, respectively. The small number of high-resolution studies combined with the heterogeneity of the analyses has motivated us to undertake an in-depth study of bright OB stars with high rotational velocities.…”
Section: Rationale Of Our Studymentioning
confidence: 99%
“…Martins et al 2010) and the effects of stellar winds are of secondary importance (e.g. Martins et al 2012).…”
Section: Bubbles North Of η Car (Nb)mentioning
confidence: 99%